The impact of migration on political, social, cultural and economic stability in Europe (Journal of Philosophy Culture and Political Science, 2019)
The article analyzes the influence of migration processes on political, social, cultural and economic stability in Europe. Considered the components of the immigration policy of the EU. The main purpose of the article is to study the factors leading to the intensification of migration processes and their impact on the social, political, cultural and economic consequences for the country; studying the mechanisms of legal regulation of the problem of migration. As a theoretical basis of the work selected studies of domestic and foreign scientists in the field of migration. As a methodological tools used general scientific research methodology: a method of analysis and synthesis, the laws of inference. In the article, we single out the reasons that prompted intellectual emigration, or «brain drain.» Economic factors are important here: unsatisfactory wages, poor material and technical base of theoretical and applied research, insufficient access to the achievements of foreign colleagues and contacts with them, caused by limited fundingof scientific and technical activities. Political reasons mainly exist when it comes to forced emigration,which causes flows of refugees of various kinds. One of the types of political reasons for emigration areethnic intrastate conflicts and civil wars implicated in class, regional, ideological contradictions or powerstruggles. Educational reasons include the desire to get an education abroad, inaccessible at home, toimprove their professional qualification level, to learn a foreign language in order to use their educationin the prospects for further development both at home and abroad.Key words: migration policy, migration processes, the European Union, stability.